Synthesis of zinc oxide nanorods: seed layer annealing effect on electrical conductivity - Iqbal, Younas (2018)
Orientation of zinc oxide nanorods has a vital role in the performance of nanoscaled-based optoelectronic devices and biosensing. In spite of a lot of research, there is no clear mechanism for the growth and orientation of ZnO nanorods during hydrothermal deposition. Beside the other properties of ZnO nanorods the electron transport properties and electron conduction are very important, in successful immobilization of various biomolecules in the field of biosensing. In current study the orientated ZnO nanorods were fabricated through hydrothermal method from a lowest possible precursor concentration. The precursors concentration was varied from 1 to 9 mM at constant deposition time (6 hours) and temperature (90◦ C), on annealed (500 ◦C) and un annealed gold seed layers. The mean square roughness of annealed and un annealed seed layers are 6.711 and 8.839 nm respectively. The morphological study of the prepared ZnO nanorods revealed a clear improvement in orientation of ZnO nanorods grown on annealed seed layer compared to un annealed seed layer. The structural characterization through XRD reveals that there is a clear peak (002) in all the concentrations on annealed seed layer. The elemental analysis showed the presence of zinc and oxygen in all concentration along with gold, which was detected from the glass substrate coated with gold. The FTIR analysis revealed very less number of bands for oriented ZnO nanorods compared to the un oriented nanorods. These analyses were confirmed by conductivity test conducting using four point probe, which shows the conductivity of oriented ZnO nanorods grown on annealed gold seed is very much higher (up to 90.909 S/m) than the un oriented ZnO nanorods (maximum value 11.574 S/m) grown on un annealed gold seed layer. From the results it is concluded that the seed layer roughness has a vital role in orientation of ZnO nanorods which has a good effect on the electrical conductivity of ZnO nanorods.